Exchange rate policy in a small open economy: an examination of Irish experience - Massey, Patrick (Statistical and Social Inquiry Society of Ireland, 1988)
The paper looks at Irish exchange rate policy since 1979 when the Irish Pound joined the EMS. The paper argues that a fixed exchange rate link is the optimal approach for an economy such as Ireland. As the bulk of Irish foreign trade is with non EMS member countries some questions arise as to the appropriateness of the target chosen. There have been significant shifts in the pattern of trade and in the structure of Irish industry since EMS entry. It was not possible to establish that these were a direct consequence of the exchange rate policy pursued given the nature of the data available. It appears that EMS membership may not have been responsible for the drop in the inflation rate which has frequently been attributed to membership and was a primary consideration behind the decision to join. Despite its limitations it is not clear that a superior exchange rate target is available
Read before the Society, 29 October, 1987
Keywords: Exchange rate; Inflation; 314.15